2007
DOI: 10.1088/0022-3727/40/2/014
|View full text |Cite
|
Sign up to set email alerts
|

Electron induced modifications in the optical properties of polypropylene

Abstract: In this work, the effect of electron beam (EB) irradiation on polypropylene (PP) films has been studied via different techniques, namely: x-ray diffraction and UV–Vis absorption spectroscopy. The PP films were irradiated with a 1.5 MeV electron beam at doses of 5, 10, 20, 50, 70, 100 and 120 kGy. The crystallinity of the PP films was found to increase, slightly, by EB irradiation. The changes in the dipole strength, transition dipole moment, oscillator strength, optical band energy gap and activation energy ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…1). These defects give localized states in the forbidden gap resulting in the increase in the number of charge carries in the conduction band due to formation of lower energy states [31]. The gradually decrease in the values of the activation energy with increase ion fluencies confirms the previously obtained decrease in the optical energy gap values.…”
Section: Activation Energysupporting
confidence: 83%
See 1 more Smart Citation
“…1). These defects give localized states in the forbidden gap resulting in the increase in the number of charge carries in the conduction band due to formation of lower energy states [31]. The gradually decrease in the values of the activation energy with increase ion fluencies confirms the previously obtained decrease in the optical energy gap values.…”
Section: Activation Energysupporting
confidence: 83%
“…It was found that E a is inversely proportional to the He ion fluence. This gradually decrease in the values of activation energy might be attributed to the formation of clusters group [31] and/or increase in the defects (cf. Fig.…”
Section: Activation Energymentioning
confidence: 99%
“…The residual carbon left in polypropylene acquires graphite like form. Therefore, conjugation and carbonization seem to be main process responsible for decrease in the band gap of polypropylene [9,16].…”
Section: Methodsmentioning
confidence: 99%
“…This is used in many applications such as radiation-sterilized medical and pharmaceutical components, food packaging materials and cosmetics [5]. A literature survey [6][7][8][9][10][11] indicates that effects of 14.89 MeV electron irradiation on polyethylene and polystyrene in the dose range of 57.6-576 KGy showed a greater red shift in absorption edge of polyethylene as compared to polystyrene [6]. Whereas, the enhancement in the thermal properties, dielectric constant, dielectric loss and crystallinity of 2 MeV and 1.5 MeV electron irradiated polypropylene has also shown considerable modifications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In this research, the oscillator strength of caffeine in distilled water and dichloromethane was calculated by absorption measurements. Oscillator strength was related to the molar decadic absorption coefficient by the following equation (Forsman & Clark, 1973;Georgakopoulous, Grondelle, & Zwan, 2004;Radwan, 2007):…”
Section: Measurement Of Integrated Absorption Cross-section and Oscilmentioning
confidence: 99%